XXXII Krytyczna Konferencja Prawnicza, Uniwersytet Warwick, Coventry, 1–3 września 2017 r. - Mańko, Rafał; Sadowski, Mirosław M.; Święcicka, Paulina (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The 32nd Critical Legal Conference, which took place at Warwick University from the 1st to 3rd of September, was organised on the theme „Catastrophe.” Of the 24 streams that have been organised, the authors chose two for full inclusion in this report: „Approaching catastrophes: exception, revolution and the law,” and „Legal globalisation and the decolonial turn: power and encryption,” along with the plenary sessions. After recounting all of the papers presented during these streams, R. Mańko, M.M. Sadowski, and P. Święcicka offer their observations on the conference
Keywords: CLC 2017; Critical Legal Conference; critical legal studies; Agamben; postcolonialism